Characterization of Celecoxib β-Cyclodextrin Inclusion Complexes Using Solvent Evaporation Method - Rosaini, Henni; Sandra, Novena; Halim, Auzal (Asian Journal of Pharmaceutical Research and Development, 2021)
Celecoxib is a non-steroidal anti-inflammatory drug (NSAID) used for the treatment of pain and inflammation. Celecoxib is included in class II in the Biopharmaceutis ClassificationAsystem drug (BCS) which has low solubility and high permeability. This study aims to increase the solubility and dissolution rate of celecoxib by characterizing the inclusion complex of celecoxib β-cyclodextrin. Inclusion complexes were prepared by the solvent evaporation method using a water-soluble polymer, β-cyclodextrin. The inclusion complexes were prepared in a 1: 1 ratio between celecoxib and β-cyclodextrins. As a comparison, a physical mixture with the same composition was made. Powder mixtures of physics and inclusion complexes characterized by physicochemical properties include: FT-IR spectroscopy analysis, DSC analysis, assay and dissolution test. The dissolution test was determined by the paddle method. The results of characterization of the inclusion complex using FT-IR spectrophotometry showed a shift in the wave number as well as the physical interaction between celecoxib and β-cyclodextrin. The results of the DSC (Differential Scanning Calorimetry) decreased the enthalpy and melting point between celecoxib, the physical mixture and the inclusion complex. The dissolution test showed an increase in dissolution rate at 60 minutes, namely Celecoxib 55.03%, physical mixture 61.58% and inclusion complex 67.53%.